Long Non-coding RNA Expression Profiling Identifies a Four-Long Non-coding RNA Prognostic Signature for Isocitrate Dehydrogenase Mutant Glioma - Chen, Yusheng; Guo, Yang; Chen, Hang; Ma, Fengjin (Frontiers in Neurology, 2020)
Background: Isocitrate dehydrogenase (IDH) mutant is one of the most robust and important genetic aberration in gliomagenesis. However, the underlying regulation mechanism of lncRNA in IDH mutant glioma has not been systematically portrayed. Methods: In this work, the RNA-sequencing data and clinical data were collected from 325 samples in the Chinese Glioma Genome Atlas (CGGA) database, 627 samples in TCGA database and 214 from GSE16011. R language and GraphPad Prism software were applied for the statistical analysis and graph work. Results: By comparing the differentially lncRNA genes between IDH mutant and IDH wild-type glioma samples, four lncRNA genes (JAG1, PVT1, H19 and HAR1A) were identified as prognostic factors in three independent databases. The risk signature model was established based on the expression level and the regression coefficient of the four lncRNA genes. IDH mutant glioma could be successfully stratified into distinct prognostic groups in CGGA, TCGA and GSE16011 databases. When combined with the clinical factors, the four-lncRNAs risk signature exhibited superior predictive value. Moreover, the biological functional analysis revealed the latent regulation mechanism of four-lncRNAs risk signature. Conclusion: Taken together, our study established a four-lncRNAs risk signature as a novel classifier for IDH mutant glioma. We revealed that the four-lncRNAs risk signature was potentially involved in immune response and tumor metabolism and may provide therapeutic targets for IDH mutant glioma patients.